The application of choice experiments in the analysis of visitors preferences for ecotourism facilities and services in Redang Island Marine Park. - Yacob, Mohd Rusli; Shuib, Ahmad; Mamat, Mohd Farid (Universiti Malaysia Sarawak, 2009)
This paper estimates the visitor's' preferences of ecotourism facilities and services in the Redang Island Marine Park (RIMP) by using choice experiments (CE). Personal interviews were conducted with a total of 298 visitors of RIMP. The visitors were asked to select the best of ecotourism facilities and services from a given set of alternatives. Investigation on the ecotourism facilities and services attributes were done on accessibility to RIMP, provision of interpretive trail, provision of information and extra package price. The conditional logit (CL) model was used to estimate visitors' preferences. Results of the study showed that visitor's preferences of facilities and services varied according to changes in attributes levels. Results of this study are important in assisting policy makers in the management and development of ecotourism facilities and services in RIMP. This study shows that choice experiments are useful tools in the investigation of visitors' preferences for the ecotourism facilities and services in marine park.